Faktor-Faktor yang Mempengaruhi Produksi Cabai (Capsicum Frutescens L.) di Desa Cipetir Kecamatan Kadudampit Kabupaten Sukabumi - Athoriq, Fikri Fauzan; Ashrul Tsani; Endang Triastutiningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to analyze the factors affecting cayenne pepper (Capsicum frutescens L.) production in Cipetir Village, Kadudampit District, Sukabumi Regency. A quantitative research method with a survey approach was employed. The sampling technique used purposive sampling involving 30 cayenne pepper farmers who were actively engaged in farming activities. The data consisted of primary data obtained through interviews and questionnaires, as well as secondary data collected from literature reviews and other supporting sources. Data analysis was conducted using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS), supported by F-tests, t-tests, and the coefficient of determination (R²). The results showed that, simultaneously, seed use, fertilizer use, and land area had a significant effect on cayenne pepper production, with an F-value of 69.173 and a significance level of less than 0.001. Partially, land area had a positive and significant effect on cayenne pepper production, with a regression coefficient of 0.507 and a significance value of less than 0.001. Meanwhile, seed use and fertilizer use did not have a significant effect on cayenne pepper production. The coefficient of determination (R²) of 0.889 indicates that 88.9% of the variation in cayenne pepper production can be explained by the three independent variables, while the remaining 11.1% is influenced by other factors outside the research model. Therefore, land area was identified as the most dominant factor affecting cayenne pepper production in Cipetir Village, Kadudampit District, Sukabumi Regency.